Spatial dynamics of a population with stage-dependent diffusion - Azevedo, F.; Coutinho, R. M. [UNESP]; Kraenkel, R. A. [UNESP] (Elsevier B.V., 2015)
We explore the spatial dynamics of a population whose individuals go through life stages with very different dispersal capacities. We model it through a system of partial differential equations of the reaction-diffusion kind, with nonlinear diffusion terms that may depend on population density and on the stage. This model includes a few key biological ingredients: growth and saturation, life stage structure, small population effects, and diffusion dependent on the stage. In particular, we consider that adults exhibit two distinct classes: one highly mobile and the other less mobile but with higher fecundity rate, and the development of juveniles into one or the other depends on population density. We parametrize the model with estimated parameters of an insect species, the brown planthopper. We focus on a situation akin to an invasion of the species in a new habitat and find that the front of invasion is led by the most mobile adult class. We also show that the trade-off between dispersal and fecundity leads to invasion speed attaining its maximum at an intermediate value of the diffusion coefficient of the most mobile class. (C) 2014 Elsevier B.V. All rights reserved.
Keywords: Reaction-diffusion equations; Invasion speed; Stage structure; Wing dimorphism